Career Commitment Based on Career Identity Diffusion among Students in Vocational Higher Education - Muhammad Hasim; Nur Fadhilah Umar; Amiruddin Amiruddin; Abdullah Sinring (Yayasan Keluarga Guru Mandiri, 2023)
Established student career identity is proven to influence individual career commitment. However, several research results show that some career identities still need to be established and have high commitment. This study aims to examine the effect of individual career commitment on career identity diffusion in vocational students. This study is a quantitative correlational research design that examines the effect of X1: social standards, X2; financial benefit, X3: functional benefit to variable Y; Career Identity Diffusion which is analyzed using multiple regression analysis. The population in this study were vocational students at Universitas Negeri Makassar. A sample of 210 students participates in the study. The instruments in this study consisted of 2, namely the Career Identity Development Inventory (CIDI) and the Career Development Questionnaire, which have been tested for validity and reliability through the Confirmatory Factor Analysis test. This study's findings indicate that financial and functional benefits are the main considerations for students who have a career diffusion identity to remain in their majors. This finding contributes to the fact that students tend to choose majors because of the high salary they will get in the future and the desire to fulfill their parents' expectations as successful people. The findings of this research are expected to be a consideration in implementing career guidance in schools, especially for teachers at vocational high schools and Counseling Guidance Teachers, so that effective career guidance since middle school will help students develop a more positive career identity.